A Review Paper on Load-Deflection Behaviour of Kenaf Fibre Reinforced Concrete Beam and Slab - Solahuddin, Azuwa (IJISET, 2021)
Concrete is primarily made up of cement, sand, coarse aggregate and water. Kenaf fibre is a natural fibre used in strengthening reinforced concrete beam and slab to enhance structural strength and ductility. This paper presents the experimental study results of load-deflection behaviour of kenaf fibre reinforced concrete beam and slab. This article addresses the experimental parameters includes load-deflection of beam and slab reinforced with kenaf fibre. Load-deflection data results are compared with each other. It is observed that kenaf fibre improves the load-deflection of reinforced concrete beam and slab. This study indicates that kenaf fibre will benefit by using it as additional material in reinforced concrete beam and slab productions.